Expression of antimicrobial drug tolerance by attached communities of Mycobacterium tuberculosis. Issue 3 (24th February 2014) - Ackart, David F.; Hascall‐Dove, Laurel; Caceres, Silvia M.; Kirk, Natalie M.; Podell, Brendan K.; Melander, Christian; Orme, Ian M.; Leid, Jeff G.; Nick, Jerry A.; Basaraba, Randall J.
Abstract There is an urgent need to improve methods used to screen antituberculosis drugs. An in vitro assay was developed to test drug treatment strategies that specifically target drug‐tolerant Mycobacterium tuberculosis. The H37Rv strain of M. tuberculosis survived antimicrobial treatment as attached microbial communities when maintained in tissue culture media (RPMI‐1640) with or without lysed human peripheral blood leukocytes. When cultured planktonically in the presence of Tween‐80, bacilli failed to form microbial communities or reach logarithmic phase growth yet remained highly susceptible to antimicrobial drugs. In the absence of Tween, bacilli tolerated drug therapy by forming complex microbial communities attached to untreated well surfaces or to the extracellular matrix derived from lysed human leukocytes. Treatment of microbial communities with DNase I or Tween effectively dispersed bacilli and restored drug susceptibility. These data demonstrate that in vitro expression of drug tolerance by M. tuberculosis is linked to the establishment of attached microbial communities and that dispersion of bacilli targeting the extracellular matrix including DNA restores drug susceptibility. Modifications of this in vitro assay may prove beneficial in a high‐throughput platform to screen new antituberculosis drugs especially those that target drug‐tolerant bacilli.